Does atrial fibrillation increase the risk of fractures? A systematic review and meta-analysis - Chen, Wei; Zhang, Yuyu; Xie, Huaze; Guo, Haiyi; Gong, Yangfan; Yin, Zhuohao; Zhao, Kai; Ge, Wei (Frontiers in Medicine, 2025)
ObjectivesWe have observed in clinical practice that patients with fractures often have concomitant atrial fibrillation. However, it remains unclear whether atrial fibrillation increases the risk of bone fracture. A meta-analysis was performed to investigate the association between atrial fibrillation and fracture.MethodsPubMed and Cochrane Library were searched for relevant studies from 1 January 1943 to 31 December 2024 that compared the prevalence of fracture in atrial fibrillation group with non-atrial fibrillation group.ResultsA total of five cohort studies with 187,868 participants met all the eligibility criteria for our study. A total of 835 people suffered a fracture in atrial fibrillation group and 6,512 in non-atrial fibrillation group. The overall risk of fractures was non-statistically higher in patients with 5.4% (835/15,395) in atrial fibrillation group and 3.8% (6,512/172,473) in non-atrial fibrillation group. Analysis of included studies observed non-significant association between atrial fibrillation and fractures [odds ratio (OR) = 1.17, 95% confidence interval (CI) = 0.60–2.29, P = 0.65]. However, subgroup analysis displayed that Asian population with atrial fibrillation had a higher risk of fracture (OR = 1.61, 95% CI = 1.38–1.87, P < 0.00001), whereas no similar outcomes were seen in Caucasian population (OR = 0.94, 95% CI = 0.24–3.59, P = 0.92).ConclusionThe evidence indicated that Asians with atrial fibrillation were more prone to fractures.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD42018107794.